2020
DOI: 10.1103/physrevd.101.045017
|View full text |Cite
|
Sign up to set email alerts
|

General relativistic quantum optics: Finite-size particle detector models in curved spacetimes

Abstract: We propose a fully covariant model for smeared particle detectors in quantum field theory in curved spacetimes. We show how effects related to accelerated motion of the detector and the curvature of spacetime influence the way different observers assign an interaction Hamiltonian between the detector and the field. The fully covariant formulation explicitly leaves the physical predictions of the theory invariant under general coordinate transformations, hence providing a description of particle detector models… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(111 citation statements)
references
References 53 publications
3
108
0
Order By: Relevance
“…With our formulation one can compute the transition probabilities according to sums over Feynman diagrams. This formulation is also fully covariant and naturally adapted to curved spacetimes, reinforcing the results of [23] that the pointlike version of the UDW model is fully covariant. We have shown that the probability amplitude associated with UDW detectors can be related to a line defect.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…With our formulation one can compute the transition probabilities according to sums over Feynman diagrams. This formulation is also fully covariant and naturally adapted to curved spacetimes, reinforcing the results of [23] that the pointlike version of the UDW model is fully covariant. We have shown that the probability amplitude associated with UDW detectors can be related to a line defect.…”
Section: Resultssupporting
confidence: 66%
“…The simplest and most famous model of a particle detector is the UDW model [9,22]. It consists of a two-level quantum system that interacts linearly with a quantum scalar field, and can potentially be used in curved spacetimes [23][24][25][26][27]. Although the smeared version of the UDW detector can be appealing for physical reasons [23,28,29], it has recently been shown that these are only covariant to lowest order in perturbation theory, and therefore cannot be used in fundamental descriptions [28].…”
Section: The Udw Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…8 We also fix the proper times of each detector τ A , τ B such that τ A = τ B = 0 when the Schwarzschild time t = 0, which is possible because the spacetime admits a Cauchy surface given by constant-t slices. We note that due to pointlike nature of the detectors, the derivative coupling particle detector model adopted here is fully covariant [45,46]. For weak coupling, we can perform a Dyson series expansion…”
Section: Jhep08(2020)155mentioning
confidence: 99%
“…We work in two spacetime dimensions, for the technical reason that this allows us to analyse the response of an Unruh-DeWitt detector operating for a finite time in a time-dependent geometry without having to smear the detector in time or in space. We expect similar phenomena due to the choice of the quantum state and due to the detector's motion to be present also in higher spacetime dimensions, but there these phenomena will be necessarily blurred by choices that will need to be made for smearing the detector's profile in time or in space [20,21].…”
Section: Introductionmentioning
confidence: 99%